Aplikasi Bimbingan Konseling Menggunakan CodeIgniter (CI) - Rafif Naufal Isad - (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2024)
At Padas 1 Public Junior High School, student violations were recorded by picket officers and Counseling Guidance teachers. The recording was carried out by the officer by writing it on a piece of paper form. Based on these problems, a guidance and counseling application was created using the codeigniter framework at SMPN 1 Padas based on a website. This system was created and developed using the waterfall method and the testing method using blackbox testing. The system created can add data, manage violation data, add attendance data and several other features. It is hoped that the system that has been created can help counseling teachers manage student counseling to be more efficient and effective, as well as make it easier for parents to supervise their children. The results of system testing using black box testing of the counseling guidance application system are made to get a success percentage of 100%.